2022
DOI: 10.3390/hydrology9110190
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effects of Porosity, Hydraulic Conductivity, Strength, and Flow Rate on Fluid Flow in Weakly Cemented Bio-Treated Sands

Abstract: Fluid injection in a porous medium is the underlying mechanism for many applications in the fields of groundwater hydraulics, hydrology and hydrogeology, and geo-environmental engineering and in the oil and gas industry. Fluid flow experiments in porous media with a viscous fluid at varying injection rates were conducted in a modified Hele-Shaw setup. The granular media were three-dimensional bio-cemented sands of various grain sizes across various cementation levels, generating a matrix of various hydraulic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 78 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…In addition, the PTFE matrix is in a viscous flow state during high temperature sintering. The different molding pressure before sintering affects the formation, growth and migration of bubbles in the composite, thus affecting the size of void in the composite, 47 affecting the compactness of the composite, and further affecting the synergistic effect of organic and inorganic components on the properties of the composite. The study by Fan et al 48 also showed that the interfacial adhesion between GF and PTFE plays a key role in the wear resistance of GF-filled PTFE composites.…”
Section: Effect Of Different Molding Pressure Processes On the Tribol...mentioning
confidence: 99%
“…In addition, the PTFE matrix is in a viscous flow state during high temperature sintering. The different molding pressure before sintering affects the formation, growth and migration of bubbles in the composite, thus affecting the size of void in the composite, 47 affecting the compactness of the composite, and further affecting the synergistic effect of organic and inorganic components on the properties of the composite. The study by Fan et al 48 also showed that the interfacial adhesion between GF and PTFE plays a key role in the wear resistance of GF-filled PTFE composites.…”
Section: Effect Of Different Molding Pressure Processes On the Tribol...mentioning
confidence: 99%
“…[168] Numerical simulations of artificial rock properties and fluid flow numerical experiments. [169] Fluid flow experiments in porous media for hydrological applications. [170,171] Fluid flow experiments in porous media for reservoir engineering applications.…”
Section: Applications Of Micp Related To Studies Involving Artificial...mentioning
confidence: 99%
“…Moreover, although both RF and ANN appear as "black boxes", RF allows a more straightforward interpretation of the factors affecting the prediction. RF algorithms have been used with promising results in several research fields related to hydraulics and hydrology [29], such as pipe breaks in water supply networks [30], water flow in porous media [31], flooding [32] and drought [33] events. RF applications in soil water erosion studies are limited in the literature and, therefore, can be considered quite innovative.…”
Section: Introductionmentioning
confidence: 99%